Mixture of natural fiber with gypsum to improve the fire resistance rating of a fire door: The effect of kapok fiber - Azieyanti N.A.; Hakim A.; Hasini H. (Institute of Physics Publishing, 2023)
Doors; Fibers; Glass; Gypsum; Mixtures; Natural fibers; Protective coatings; Rating; Wool; Yarn; Fire doors; Fire resistance rating; Fire resistant; In-fiber; Kapok fibers; Fire resistance